2020
DOI: 10.1177/1461444820962452
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-sexting as mediated intimacy work: ‘Putting something on the line’

Abstract: This article is concerned with women’s digitally mediated practices of creating and sending private sexual images to men, here referred to as ‘hetero-sexting’. Drawing on material from individual interviews with adult British women about their experiences of hetero-sexting, the article develops an understanding of women’s hetero-sexting practices as a form of female-conducted ‘mediated intimacy work’, constituted by a constant negotiation of female risk taking and male trustworthiness. In doing so, it shows ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Naturally, making oneself vulnerable always carries the risk of being exposed by untrustworthy interaction partners, online and offline. Yet, it is especially this vulnerability that establishes trust and connection (Amundsen, 2020 ). So, instead of demonizing sexting as such, research should begin to investigate its functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturally, making oneself vulnerable always carries the risk of being exposed by untrustworthy interaction partners, online and offline. Yet, it is especially this vulnerability that establishes trust and connection (Amundsen, 2020 ). So, instead of demonizing sexting as such, research should begin to investigate its functions.…”
Section: Discussionmentioning
confidence: 99%
“…As fear of contagion and pandemic mitigation measures forced individuals to minimize physical contact (Dunford, 2020 ), technology-mediated communication gained importance in satisfying the need for intimacy (Ballester-Arnal et al, 2020 ). One way to be intimate without physical contact is sexting, i.e., the exchange of sexually suggestive or explicit texts and (semi-)naked photographs via mobile phones and social media (Albury et al, 2013 ; Amundsen, 2022 ). Research has shown that during the first COVID-19-related lockdown, some people were willing to add sexting to their sexual repertoire (Lehmiller et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study build on existing work 22 to show that people's digital sexual experiences are often about engaging sexual intimacies, and that pleasure and connection are part of many people's online sexual experiences, even where risks are present. 1,10,29 As we know from decades of research on sexual health education, [62][63][64] people's choices and actions in sex and relationships rarely stem from simple, rational choices about risk and safety. Rather, choices and actions sit within a context of social, cultural and sexual practices and pleasures, as well as gendered relationships and patterns of inequality.…”
Section: Discussionmentioning
confidence: 99%
“…The literature cited above suggests that the benefits of digital technologies can best be understood in the context of human relationships and intimacy, the pursuit of sexual pleasure, or to explore sexual identity and seek information and support for this. 1,4,22,29,30 The form and function of the technology is significant in that the internet enables affordable, accessible connection and the small, portable nature of smart devices enables constant and spontaneous communication, often involving visual communication via photos or video. 4,24,25 However, the functionality of devices or platforms does not wholly determine people's use or experiences of technology within their sex or intimate lives.…”
Section: Introductionmentioning
confidence: 99%